The Second-Order Optimality Conditions for Variable Programming (Journal of Computational Mathematics, 2018)
We study in this paper the continuity of the objective function for variable programming. In particular, we study the second-order optimality conditions for unconstrained and constrained variable programming. Some new second-order sufficient and necessary conditions are obtained.